Disabled people in Britain and the impact of the COVID‐19 pandemic. (11th August 2021) - Shakespeare, Tom; Watson, Nicholas; Brunner, Richard; Cullingworth, Jane; Hameed, Shaffa; Scherer, Nathaniel; Pearson, Charlotte; Reichenberger, Veronika
Abstract: This paper reports on in‐depth qualitative interviews conducted with 69 disabled people in England and Scotland, and with 28 key informants from infrastructure organisations in the voluntary and statutory sectors, about the impact of COVID‐19, and measures taken to control it. Participants were recruited through voluntary organisations. As with everyone, the Pandemic has had a huge impact: we discuss the dislocations it has caused in everyday life; the failures of social care; the use of new technologies; and participants' view on leadership and communication. We conclude with suggestions for urgent short term and medium term responses, so that the United Kingdom and other countries can respond better to this and other pandemics, and build a more inclusive world.